St. Kitts and Nevis : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in St. Kitts and Nevis during 1995-96. Output performance was robust in 1996, showing a strong recovery from hurricanes Luis and Marilyn, which damaged the country in September 1995. Real GDP growth was 5.8 percent in 1996, compared with 3.7 percent in 1995, largely because of a strong rebound in agriculture and tourism and related sectors. Domestic expenditures increased an average of 10 percent a year over 1995-96. The increase in 1995 reflects a surge in both public and private capital expenditures following the hurricanes.